Review: Applications of surface-enhanced fluorescence (SEF) spectroscopy in bio-adetection and biosensing (2020)
Surface-enhanced fluorescence (SEF) is rapidly becoming one of the main spectroscopic techniques for the detection of a variety of biomolecules and biomarkers. The main reasons for this trend are the high sensitivity and selectivity, robustness, and speed of this analytical method. Each year, the number of applications that utilize this phenomenon increases and with each such work, the complexity and novelty of the used substrates, procedures, and analytes rises. To obtain a clearer view of this phenomenon and research area, we decided to combine 76 valuable research articles from a variety of different research groups into this mini-review. We present and describe these works concisely and clearly, with a particular interest in the quantitative parameters of the experiment. These sources are classified according to the nature of the analyte, on the contrary to most reviews, which sort them by substrate nature. This point of view gives us insight into the development of this research area and the consequent increase in the complexity of the analyte ature. Moreover, this type of sorting can show possible future routes for the expansion of this research area. Along with the analytes, we can also pay attention to the substrates used for each situation and how the development of substrates affects the direction of research and subsequently, the choice of an analyte. About 108 sources and several interesting trends in the SEF research area over the past 25 years are discussed in this mini-review.